Length-Weight Relationship And Condition Factor Of Mangrove Fish Species In Azagny National Park (Grand-Lahou Department, Ivory Coast) - Kouadio Kouassi Alain; Yao Stanislas Silvain; Kamelan Tanoh Marius; Konan Yao Aristide (European Scientific Journal, ESJ, 2022)
The length-weight relationship and condition factor of mangrove fish species in Azagny National Park (ANP) were studied, to provide baseline data of the impact of mangrove disturbances on ichthyofauna. Specimens were captured from March 2019 to February 2020 using gillnets and mesh traps. After identification, each specimen was weighed to the nearest gram and measured to the nearest millimeter. Twenty-eight species belonging to 17 families and 24 genera were selected based on their numbers (only species with at least 10 specimens were considered). Most of these species have a negative allometry (22 species, 78.57%). 14.28% species showed positive allometry and 7.14% species showed isometry. The length-weight regressions are significant with a coefficient of determination (r²) varying between 0.115 for Chrysichthys maurus and 0.936 for Labeo coubie. The coefficient of allometry b varies from 0.413 for Chrysichthys maurus to 4.272 for Labeo coubie with a mean value of 2.384 ± 0.810. The condition factor ranged on average from 0.935 ± 0.966 for Schilbe mandibularis 113.3 ± 10.644 for Chrysichthys maurus. This study provides information on the effects of mangrove disturbance on the growth of species of the said ecosystem and contributes to the management of the ichthyofauna of the ANP.